80 GENETIC MYOCARDITIS: ADVANCED WORKUP AND TREATMENT. (15th December 2022) - Peretto, Giovanni; De Luca, Giacomo; Villatore, Andrea; Sala, Simone; Di Resta, Chiara; Palmisano, Anna; Vignale, Davide; Campochiaro, Corrado; De Gaspari, Monica; Rizzo, Stefania; Busnardo, Elena; Ferro, Paola; et al.
Abstract: Background: Preclinical data support the rationale for targeting myocardial inflammation in genetic nonischemic cardiomyopathies. However, no consistent clinical reports have been provided so far. Methods: We describe a series of patients (n=25) with genetic cardiomyopathy and active myocardial inflammation (AMI) proven by multimodal diagnostic workup. Patient-tailored immunosuppressive therapy was empirically started to target myocardial inflammation whenever feasible. Multiple outcomes were retrospectively assessed by a dedicated multidisciplinary disease unit. Results: Patients carrying desmosomal (DGV), cytoskeletal (CGV) and membrane gene variants (MGV), were 12 (48%), 10 (40%), and 3 (12%), respectively. DGV carriers uniformly presented with myocarditis-like chest pain and ventricular arrhythmias, whereas heart failure symptoms were found only in CGV carriers. Dilated cardiomyopathy phenotype and ring-like pattern on cardiac magnetic resonance allowed the best discrimination among genotypes. AMI was proven by endomyocardial biopsy in all cases, and by noninvasive imaging in 21 (83%). IST was started in 17 patients (71%) with no safety issues. By the end of follow-up (median 69 months, range 21-182), signs of AMI were documented in 6/18 IST receivers (33%) and 4/7 untreated cases (57%). For most genotypes, paucity of adverse events was noted while on immunosuppression as compared to the off-treatment period. Conclusion: Our preliminary data provide the clinical rationale for the research and targeting of AMI in a spectrum of genetic nonischemic cardiomyopathies.